1997
DOI: 10.3171/jns.1997.87.6.0921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ifenprodil, a polyamine site NMDA receptor antagonist, on reperfusion injury after transient focal cerebral ischemia

Abstract: Polyamines and N-methyl-D-aspartate (NMDA) receptors are both thought to play an important role in secondary neuronal injury after cerebral ischemia. Ifenprodil, known as a noncompetitive inhibitor of polyamine sites at the NMDA receptor, was studied after transient focal cerebral ischemia occurred. Spontaneously hypertensive male rats, each weighing between 250 and 350 g, underwent 3 hours of tandem middle cerebral artery (MCA) and common carotid artery occlusion followed by reperfusion for a period of 3 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 38 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…12,13 However, the bases of the neuroprotective action of these drugs at cellular and synaptic level are still unknown. To our knowledge, this study represents the first demonstration that NR2B subunit antagonists block postischemic LTP, favoring the recovery of activitydependent LTP in the ischemic penumbra.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, the bases of the neuroprotective action of these drugs at cellular and synaptic level are still unknown. To our knowledge, this study represents the first demonstration that NR2B subunit antagonists block postischemic LTP, favoring the recovery of activitydependent LTP in the ischemic penumbra.…”
Section: Discussionmentioning
confidence: 99%
“…In animal neuroprotection studies, ifenprodil is commonly used at a dose of 10 mg/ kg (Dogan et al, 1997); we found that doses of 20-30 mg/kg of ifenprodil were need to control prolonged SE in 28% of animals. As mentioned, ifenprodils dose-response curve was flat, with incremental doses causing limited effect.…”
Section: Discussionmentioning
confidence: 99%
“…Brain water content as an indicator of brain edema was measured at 24 h after TBI according to the previous report (Dogan et al, 1997). As shown in Fig.…”
Section: Fty720 Provided Neuroprotection After Tbimentioning
confidence: 99%